Estudo da viabilidade do uso de métodos de segunda ordem e RMN na elaboração de fingerprint de bauhinia forficata baseado em seu extrato bruto - Assis, Priscylla Rodrigues (2014)
Given the large number of species of Bauhinia and great morphological similarity between them, it is necessary the development of robust analytical techniques in quality control of plants used as herbal medicines, since it is difficult to achieve the desired effects when using a different species as is the case of plant studied. Therefore, this study aimed to identify similarities between commercial preparations and the standard sample Bauhinia forficata Link. Obtained crude extracts of commercial samples and standard sample using different extracting phases. The extracts were analyzed using the technique of nuclear magnetic resonance (NMR) and principal component analysis (PCA) used for extraction and interpretation of the data obtained. As a result, we found that the extracting phases hexane, methanol and methanol / water, generated the most varied spectral profiles. Visual analysis of the samples suggests that there are at least four different samples in the data set. Moreover, by analyzing PCA can be concluded that all the samples are different from the standard sample. However, it is not possible to say whether or not the samples belong to the same species, since external causes as time and storage temperature, can cause chemical variability that are modeled by the PCA and thus further studies should be conducted in order to classify them. To do this we studied the feasibility of using second-order methods such as PARAFAC and MCR. The characteristics data didn t accord the requirements for use of these methods, such as trilinearity, blocking its application.